2016
DOI: 10.17795/ajdr-29026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Whole Salivary Lactate Dehydrogenase Level in Patients With and Without Periodontal Disease

Abstract: Background: Tracking various biomarkers in serum, gingival crevicular fluid (GCF), and saliva has been introduced as a diagnostic tool for periodontal disease detection. Objectives: The aim of this study was to compare salivary lactate dehydrogenase (LDH) levels in subjects with periodontal disease and levels in subjects without periodontal disease. Materials and Methods:In this case-control study, 170 patients at Hamadan faculty of Dentistry, including patients with periodontal disease and patients with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, previous research has confirmed that gender does not significantly affect LDH levels, either among patients with periodontal disease or those with normal periodontia. 23 Finally, the current study was designed with strict inclusion criteria; thus, the exclusion of potential subjects may have hampered the generalisability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has confirmed that gender does not significantly affect LDH levels, either among patients with periodontal disease or those with normal periodontia. 23 Finally, the current study was designed with strict inclusion criteria; thus, the exclusion of potential subjects may have hampered the generalisability of the results.…”
Section: Discussionmentioning
confidence: 99%